TANGGUNGJAWAB NEGARA PENYOKONG TERORISME TERHADAP STATE SPONSORED TERRORISM DALAM HUKUM INTERNASIONAL - NIM. A1011211152, RIZZKI ZAKI WIDODO (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract State-sponsored terrorism may be defined as acts of terrorism that are supported by a state. Such support may take the form of active assistance, including financing, protection, or training, as well as passive support, such as omission or negligence. The regulation of state-sponsored terrorism within international law remains highly limited. This limitation refers to the absence of clear mechanisms and well-defined forms of state responsibility when addressing state-sponsored terrorism, despite the fact that it is not a new phenomenon in international relations. This research examines the ambiguity of legal responsibility of states that support state-sponsored terrorism under international law, with reference to two principal cases: Libya following the 1988 Lockerbie incident and Afghanistan under the Taliban regime (1996–2001), which provided sanctuary to Al-Qaeda. The study finds that, to date, neither a comprehensive definition nor standardized mechanisms governing state-sponsored terrorism exist within international law. Consequently, the attribution of state responsibility largely relies on the theory of state responsibility, the obligation of due diligence, and the principle of aut dedere aut judicare. Through these legal frameworks, a state may be held internationally responsible if it is proven to have provided direct or indirect support to terrorist groups. Both cases demonstrate the significant role of the United Nations Security Council in determining the status of state-sponsored terrorism through its resolutions. Libya ultimately acknowledged responsibility, extradited the suspects, and paid compensation to the victims, leading to the lifting of sanctions imposed upon it. In contrast, Afghanistan refused to cooperate and continued to provide protection to Al-Qaeda, resulting in prolonged international sanctions and culminating in military intervention in 2001. From these cases, this study analyzes and explains the legal framework for holding supporting states accountable for state-sponsored terrorism, as well as the forms of responsibility that may be imposed. Keywords: State-Sponsored Terrorism, State Responsibility, International Law. Abstrak State Sponsored Terrorism dapat diartikan sebagai suatu tindakan terorisme yang didukung oleh suatu negara. Dukungan tersebut dapat berupa dukungan aktif seperti pendanaan, perlindungan, atau pelatihan, maupun dukungan pasif seperti kelalaian. Pengaturan mengenai State Sponsored Terrorism dalam hukum Internasional masihlah sangat minim. Minimnya yang dimaksud adalah belum jelasnya mekanisme dan bentuk tanggung jawab seperti apa yang dimaksud saat membicarakan State Sponsored Terrorism. Padahal State Sponsored Terrorism sendiri bukanlah fenomena baru dalam dunia Internasional. Penelitian ini membahas ketidakjelasan pertanggungjawaban hukum negara penyokong State Sponsored Terrorism dalam hukum internasional dengan referensi dua kasus utama: Libya pasca-insiden Lockerbie 1988 dan Afghanistan di bawah rezim Taliban (1996–2001) yang memberi perlindungan kepada Al-Qaeda. Dari kasus tersebut ditemukan hingga kini, definisi maupun mekanisme baku untuk mengatur State Sponsored Terrorism dalam hukum internasional belum memadai, sehingga pertanggungjawaban negara sangat bergantung pada State Responsibility Theory, kewajiban due diligence, serta prinsip aut dedere aut judicare. Melalui perangkat ini, suatu negara dapat dimintai pertanggungjawaban apabila terbukti memberikan dukungan langsung atau tidak langsung kepada kelompok teroris. Dari kedua kasus menunjukkan bahwa Dewan Keamanan PBB berperan penting dalam menetapkan status State Sponsored Terrorism melalui resolusi yang dikeluarkannya. Libya akhirnya mengakui tanggung jawab, mengekstradisi tersangka, serta membayar kompensasi kepada korban, sehingga sanksi terhadapnya dicabut. Sebaliknya, Afghanistan menolak kooperasi dan tetap melindungi Al-Qaeda, sehingga memicu sanksi internasional berkepanjangan dan intervensi militer pada 2001. Dari kedua kasus tersebut dapat dianalisis dan dijelaskan suatu perangkat mengenai bagaimana meminta pertanggungjawaban negara penyokong terhadap State Sponsored Terrorism serta bagaimana bentuk pertanggungjawabannya. Kata Kunci: State Sponsored Terrorism, Pertanggungjawaban Negara, Hukum Internasional